2017
DOI: 10.1515/znb-2016-0199
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a macrocyclic copper complex containing the 14-membered 1,3,5,8,10,12-hexaazacyclotetradecane unit

Abstract: In this work, a new macrocyclic copper complex, [Cu(ACE)(SCN)2]; ACE: 1,3,6,10,12,15-hexaazatricyclo[13.3.1.16,10]eicosane, was prepared and characterized by elemental analysis, FT-IR, Raman spectroscopy and single-crystal X-ray diffraction. X-ray analysis of [Cu(ACE)(SCN)2] reveals an elongated octahedral geometry around the copper atom in a centrosymmetric CuN6 environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The PPTA ligand and the O-donor atoms of the nitrate ligands occupy equatorial positions [with bond lengths in the range 1.9632 (13)-1.9993 15 Table 2). The axial bond length is 0.25 Å longer than the equatorial bond lengths due to the Jahn-Teller effect (Hakimi et al, 2012(Hakimi et al, , 2017. In addition, there might be weak interactions with the O atoms of the nitrate ligands [Cu1Á Á ÁO3 = 2.884 (2) Å and Cu1Á Á ÁO6 = 2.6561 (15) Å ].…”
Section: Figurementioning
confidence: 99%
“…The PPTA ligand and the O-donor atoms of the nitrate ligands occupy equatorial positions [with bond lengths in the range 1.9632 (13)-1.9993 15 Table 2). The axial bond length is 0.25 Å longer than the equatorial bond lengths due to the Jahn-Teller effect (Hakimi et al, 2012(Hakimi et al, , 2017. In addition, there might be weak interactions with the O atoms of the nitrate ligands [Cu1Á Á ÁO3 = 2.884 (2) Å and Cu1Á Á ÁO6 = 2.6561 (15) Å ].…”
Section: Figurementioning
confidence: 99%
“…In another survey, all macrocyclic complexes of ACE were investigated. This study revealed that there are nine compounds; six ACE/Cu examples [14,15,56] and three ACE/Ni ones [57][58][59]. In all complexes, the ACE ligand act as N4-donor (N1, N5, N8 and N12, Scheme 1) except in one case [14] in which in addition to the four nitrogen atoms of ACE, one of the side nitrogen atoms of the macrocyclic ligand (N3 or N10, Scheme 1) also participates in complexation reaction.…”
Section: Description Of the Crystal Structuresmentioning
confidence: 98%